MAS and static NMR study on N–H⋯Br hydrogen bond in organic-inorganic perovskite [NH3(CH2)4NH3]CdBr4 crystal. (1st October 2022) - Lim, Ae Ran
Abstract: In-depth understanding of the physicochemical properties of organic–inorganic perovskites is essential for their applications in batteries, supercapacitors, and fuel cells. Considering its importance, the physicochemical behavior of [NH3 (CH2 )4 NH3 ]CdBr4 was analyzed in this study. The crystal structure of the material was found to be monoclinic and the phase transition temperature was determined to be 508 K. The material was thermally stable up to 580 K. Further, the 1 H and 13 C chemical shifts of the cation, as observed through nuclear magnetic resonance spectroscopy, showed no structural changes with temperature. However, the temperature-dependent 14 N chemical shifts of NH3 at both ends of the cation and the 113 Cd chemical shifts of the CdBr4 anion indicated the changes in the N–H⋯Br hydrogen bond owing to the change in the structural geometry of CdBr4 . The analyzed physicochemical properties revealed critical information regarding the basic mechanisms that will facilitate the broad-scale application of the organic–inorganic perovskite. Highlights: Organic–inorganic perovskites [NH3 (CH2 )4 NH3 ]CdBr4 . The changes in the N–H⋯Br hydrogen. Nuclear magnetic resonance for 1 H, 13 C, 14 N, and 113 Cd.